2019
DOI: 10.1111/1346-8138.15000
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between quinolone use and resistance of Staphylococcus epidermidis in patients with acne vulgaris

Abstract: Staphylococcus epidermidis is a bacterium known to inhabit the skin. In treatment of acne vulgaris, the cutaneous milieu is exposed to oral or topical antimicrobials. We previously reported that the antimicrobial resistance of Cutibacterium acnes isolated from acne patients is affected by antimicrobial use. The aim of this study was to investigate the relationship between quinolone use and resistance in skin bacteria, particularly S. epidermidis, from acne patients. A total of 92 and 87 S. epidermidis strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Given the intense interest in the biological relevance of the human microbiome, understanding how interventions may perturb the microbiome of the largest human organ over time is critically important. Although previous reports have suggested that systemic antibiotic usage can increase the prevalence of antibiotic-resistant microbes on skin (6)(7)(8), these studies focused on cultured isolates or targeted resistance genes. A limited number of skin microbiome studies have analyzed the effects of antibiotics (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Given the intense interest in the biological relevance of the human microbiome, understanding how interventions may perturb the microbiome of the largest human organ over time is critically important. Although previous reports have suggested that systemic antibiotic usage can increase the prevalence of antibiotic-resistant microbes on skin (6)(7)(8), these studies focused on cultured isolates or targeted resistance genes. A limited number of skin microbiome studies have analyzed the effects of antibiotics (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…The over-colonization of Propionibacterium acne triggers the immune response in sebocytes, keratinocytes, and monocytes [38]. In addition, the proportion of Staphylococcus increases with the severity of AV [38][39][40][41]. In this study, we found that patients with moderate-to-severe AV showed increased amounts of Staphylococcus and Propionibacterium compared with healthy controls (P = 0.013 and P = 0.0015, respectively), suggesting that the two genera could be possible biomarkers of moderate-to-severe AV and that their overgrowth may be related to the pathogenesis of acne.…”
Section: Discussionmentioning
confidence: 99%
“…Acne treatment is mainly based on severity, in which severe acne is treated mainly with oral isotretinoin and antibiotics, and could take months or even years for completion of treatment 34 . Long‐term antibiotic use may cause side effects, including dysbacteriosis and resistance to symbiotic bacteria, increasing the probability of opportunistic pathogen infection 35,36 . Long‐term use of isotretinoin may induce skin and mucous membrane dryness, elevated blood lipids, abnormal liver function, teratogenicity, depression, and suicidal tendencies.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Long‐term antibiotic use may cause side effects, including dysbacteriosis and resistance to symbiotic bacteria, increasing the probability of opportunistic pathogen infection. 35 , 36 Long‐term use of isotretinoin may induce skin and mucous membrane dryness, elevated blood lipids, abnormal liver function, teratogenicity, depression, and suicidal tendencies. Therefore, a variety of safe and effective physical therapies gradually have become the new trend in acne treatment.…”
Section: Discussionmentioning
confidence: 99%